Size Matters: Analyses of Benthic Foraminiferal Assemblages Across Differing Size Fractions - Lo Giudice Cappelli, Elena; Austin, William E. N. (Frontiers in Marine Science, 2019)
Benthic foraminiferal assemblages are the object of numerous studies spanning from (palaeo)environmental reconstructions to biomonitoring; however, the establishment of a procedure to standardize these studies remains a recent achievement. Not all studies based on benthic foraminiferal assemblages adopt the same methodology, which potentially hinders the use and comparison of samples prepared prior to the creation of a standard protocol or, indeed, without the knowledge of it. One of the main issues is to understand and possibly quantify the influence of different size fractions on foraminiferal biodiversity and richness. In this study, we analyzed benthic foraminiferal assemblages from the west coast of Shetland (Scotland), which were deliberately prepared without following the standard procedure, and were instead picked from the size fractions 63-150 m and > 150m. Based on assemblage composition, biodiversity indices and multivariate analyses of the data, we assessed the quality and precision of the environmental information that could be extrapolated from these samples. We found that general biodiversity trends remain the same regardless of size fraction, whereas the assemblage internal composition is significantly different between size fractions, with the small fraction retaining a greater degree of environmental sensitivity. We recommend compiling the two sample sets to produce a more holistic and detailed picture of environmental change and generate high-resolution environmental reconstructions. Nevertheless, we conclude that benthic foraminiferal assemblages picked from the large size fraction (> 150 µm) still provide useful information on prevailing environmental conditions and remain useful for an overview of environmental change in these coastal settings.